Development and Validation of Situational Judgement Test to Measure Continuous Learning Competency - Yunita Faela Nisa; Jahja Umar; Puspita Dian Arista; Helena Widaningrum; Bahrul Hayat (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
Measuring continuous learning (CL) competency is beneficial to achieving success for individuals and organizations. For this reason, the availability of a brief but valid instrument is crucial. This study aims to develop a valid instrument to measure the CL using a situational judgment test (SJT). The instrument was developed and validated using respondents of 502 employees at the supervisory level in the electrical industry (with age M=30.13, SD=6.17). For content validity, we first held focus group discussions with supervisors and managers to identify and develop some essential characteristics of the CL. Subject matter experts were involved in writing and reviewing the items. A confirmatory factor analysis was conducted to test the construct validity, and it was found that 12 of 13 items fitted a unidimensional model. All the factor loadings were statistically significant (p<.05). A further test for parallel assumption was done to check the tau-equivalence. This test is vital because raw scores are mostly used in daily practice rather than scaled scores. The results showed that 12 items met the tau equivalent requirement. For further research, scoring for multiple-choice SJTs using the nominal response model (NRM) could be considered since there was a tendency for some of the questions to elicit ambiguous choices.